Effect of glutamine on the immune function of paclitaxel intervention in ovarian cancer mice - Wang, Li; Li, Yanfen; Wang, Juan (Cellular and Molecular Biology, 2020)
To analyze the effect of amide Valley on the immune function of ovarian cancer mice treated with paclitaxel. Fifty SPF female BALB/c mice were selected as experimental subjects, and the mice were divided into five groups, namely normal control group, tumor control group, paclitaxel group, glutamine group and combined intervention group, with 10 mice in each group. Except for the normal control group, the other 40 mice were all subjected to ovarian cancer modeling. After modeling, the tumor control group mice were injected with saline at a dose of 25 mg/kg; the mice in the paclitaxel group were given a dose of 25 mg/kg. Intraperitoneal injection of paclitaxel; mice in the glutamine group were intraperitoneally injected with glutamine at a dose of 25 mg/kg; mice in the joint intervention group were intraperitoneally injected with glutamine and paclitaxel at a dose of 25 mg/kg once daily. The normal control mice did not receive any treatment. Observe and compare the status of the five groups of mice and regularly measure the quality of the mice; after 2 weeks of treatment, the CD3+, CD4, CD4+, CD8, CD8+ of the T lymphocyte subsets of each group of mice were detected by flow cytometry calculate the ratio of CD4 / CD8. The tumor formation rate of mouse ovarian cancer was 95% (38/40). The hair color, diet, excretion and activity of mice in the normal control group were normal, while the hair of the remaining four groups of ovarian cancer mice was sparse and dull compared with those in the normal control group, and the diet was decreased and the action was retarded. By measuring the body mass of mice at a regular time, we found that before treatment, the body mass of the other four groups of ovarian cancer mice increased significantly (P< 0.05) because of the tumor body compared with the normal control group mice; after treatment, compared with the other ovarian cancer mice group, the body mass of the combined intervention group mice decreased significantly, the difference was statistically significant (P< 0.05), suggesting that the tumor body was reduced. Compare with normal control mice, CD3+, CD4, and CD4 / CD8 of other ovarian cancer mice groups were significantly decreased, and CD8+ was significantly increased, the differences were statistically significant (P< 0.05); There was no significant difference in the levels of CD3+, CD4+, CD4 / CD8, and CD8+ between the tumor control group and the paclitaxel group (P> 0.05). Paclitaxel does not improve the immunity of patients during the treatment of ovarian cancer. Glutamine is effective immunomodulation. By regulating paclitaxel-treated ovarian cancer mice, it can simultaneously treat ovarian cancer, significantly improve the immune function of ovarian cancer mice, thereby improving the anti-tumor ability, and provide the possibility of significantly improving the body’s immunity of ovarian cancer patients. Clinical research and long-term prognosis still need to be confirmed by further studies.